Tinjauan Hukum Syariah dan Hukum Positif terhadap Sistem Denda pada Pembiayaan Syariah - Arifin, Rizal; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The fine system in Islamic financing is an important instrument to discipline customers, yet its implementation raises debates regarding compatibility with sharia principles and compliance with positive law. This research examines the fine system comparatively from sharia law and Indonesian positive law perspectives, focusing on the concepts of ta’widh, gharamah, and ta’zir, as well as harmonization between the two legal systems. Using a descriptive-analytical and comparative normative juridical approach, this research examines DSN-MUI fatwas, laws and regulations, and related academic studies. The findings reveal that in sharia law, ta’widh functions as compensation for real losses, gharamah as a moral sanction whose proceeds are channeled as social funds, and ta’zir as an educational sanction. DSN-MUI Fatwas Number 17/DSN-MUI/IX/2000, 43/DSN-MUI/VIII/2004, and 77/DSN-MUI/VI/2010 regulate these three concepts. Positive law through the Sharia Banking Law, KHES, and POJK has accommodated fine regulations operationally. However, harmonization still leaves tensions, especially in the Civil Code compensation concept which includes interest elements contradicting sharia principles, as well as the lack of understanding among judges and practitioners regarding the differences between fine concepts. This research recommends strengthening regulatory harmonization, improving law enforcement capacity, and massive socialization to industry players.